Influence of the synthesis route on optical and luminescence properties of glass-ceramic doped with europium ions - Golonko, Piotr (Photonics Letters of Poland, 2024)
The production of transparent glass-ceramic materials often faces challenges, such as inhomogeneities, inclusions, uncontrolled crystallization and other defects that make glass ceramics unsuitable for fiber optics, for example. At the same time, the chosen chemical composition is valuable for its unique properties. The present study investigated the effect of different methods of synthesizing glass-ceramic silica-germanium-antimony matrices on their transmittance optimization and luminescence properties where the conventional melt-quenching route is insufficient in terms of the transparency and homogeneity of the material obtained. The effect of heat treatment on the studied properties was also considered. Full Text: PDF References G.A. Khater, E.M. Safwat, J. Kang, Y. Yue, A.G.A. Khater, "Some Types of Glass-Ceramic Materials and their Applications", Int. J. Res. Stud. Sci. 7(3), 1 (2020). DirectLink J. Deubener, M. Allix, M.J. Davis, A. Duran, T. Höche, T. Honma, et al., "Updated definition of glass-ceramics", J. Non-Crystalline Solids 501, 3 (2018). CrossRef W. Blanc, Y. Gyu Choi, X. Zhang, M. Nalin, K.A. Richardson, G.C. Righini, et al., "The past, present and future of photonic glasses: A review in homage to the United Nations International Year of glass 2022", Progr. Mat. Sci. 134, 101084 (2023). CrossRef P. Golonko, M. Kochanowicz, P. Miluski, M. Kuwik, J. Pisarska, W. Pisarski, J. Dorosz, M. Leśniak, D. Dorosz, A. Basa, J. Żmojda, "Glass-ceramic optical fibers with controlled crystallization of core doped with europium ions", Ceram. Int. S0272884224002955 (2024). CrossRef J. Zmojda, M. Kochanowicz, P. Miluski, A. Baranowska, A. Basa, R. Jadach, M. Sitarz, D. Dorosz, "The influence of Ag content and annealing time on structural and optical properties of SGS antimony-germanate glass doped with Er3+ ions", J. Mol. Struct. 1160, 428 (2018). CrossRef X. Liu, J. Zhou, S. Zhou, Y. Yue, J. Qiu, "Transparent glass-ceramics functionalized by dispersed crystals", Progr. Mat. Sci. 97, 38 (2018). CrossRef T.N.L. Tran, A. Chiasera, A. Lukowiak, M. Ferrari, "Eu3+ as a Powerful Structural and Spectroscopic Tool for Glass Photonics", Materials 15, 1847 (2022). CrossRef Z. Li, L. Tan, C. Chen, D. Zhou, L.R. Jensen, J. Ren, Y. Zhang, J. Qiu, Y. Yue, "The effect of melt-homogenization and heat-treatment on the optical properties of the rare earth doped oxyfluoride glass-ceramics", J. Non-Cryst. Solids 593, 121773 (2022). CrossRef D. Dorosz, M. Kochanowicz, R. Valiente, A. Diego-Rucabado, F. Rodríguez, N. Siñeriz-Niembro, et al., "Pr3+-doped YPO4 nanocrystal embedded into an optical fiber", Sci Rep. 14, 7404 (2024). CrossRef